Pengaruh Tax Avoidance Terhadap Kebijakan Dividen Tunai Dimoderasi Pengungkapan Tata Kelola Perusahaan - William Chandra, Estralita Trinawati (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to obtain empirical evidence on the effect of tax avoidance to cash dividend policy with corporate governance disclosure as a moderating variable that listed in Indonesia Stock Exchange, with a total of 30 samples. This study uses secondary data which were tested using software SmartPLS 3,0. The result of this study suggests that tax avoidance have no effect to cash dividend policy and corporate governance disclosure doesn’t moderate the effect of tax avoidance on cash dividend policy